Exploring teachers' conceptions and implementation of differentiated reading in primary and elementary schools - HENEGHAN, HELEN PATRICIA (Trinity College Dublin. School of Education. Discipline of Education, 2018)
Reading is an essential life skill and an important component of learning. Effective teachers encourage and sustain children?s desire to read, restructuring teaching and learning activities to meet pupil variance towards the provision of achievable goals and meaningful learning. Demographic changes in recent years have heralded increased cultural diversity in primary, and elementary schools. Recent policy initiatives, including the Primary Language Curriculum (DES, 2015) and the ?Every Student Succeeds Act? (ESSA, 2015) have renewed focus on literacy approaches that promote literacy and accommodate pupil variance in different school contexts. Differentiated reading (DR) is one instructional model that is compatible with these literacy strategies and responds to learner variance. This study explored teachers? conceptions about DR. It investigated teachers? implementation of DR through content, process and product. It explored the implementation of learner-responsive, teacher-facilitated activities. Two case studies in diverse cultural contexts (Dublin, Ireland and Houston, Texas, US), provided data from questionnaires (n=645), lesson-plan evaluations (n=10) and interviews (n=10) with teachers located in 62 schools. Findings from qualitative data from this case study, using a sequential, mixed method design, supported survey data apart from minor exceptions, thus supporting the validity of the findings. Findings indicate that most of the teacher participants in Dublin and in Houston employed similar practices, even though they taught in different educational systems in culturally diverse contexts. The majority of teachers implemented DR because of school initiative and personal interest. Most teachers received no pre-service DR professional development while Houston teachers received more DR professional development than Dublin teachers. Teachers demonstrated a fair understanding of DR and defined DR by matching content and process to children?s individual needs and setting individual goals. Findings indicate a positive response to DR from teachers while also indicating the desire for relevant DR professional development, especially observation of effective DR lessons. Most teachers differentiated process, some modified product and fewer teachers differentiated content to meet pupil variance. The main facilitating factors in DR were individual goals, positive learning environment, and preparation and structure. The two main obstacles to DR were lack of time and class size. Recommendations are offered on school and policy level to overcome perceived obstacles. These findings can help shape future policies and guidelines for teachers, schools, professional development, and pre-service teacher education. This study is significant for a number of reasons. It provides; the explicit theoretical framing of DR in relation to Vygotsky?s ZPD; empirically explored concepts within two unique large datasets, in two diverse locations; and novel insights into teachers? conceptions and implementation of DR in the two specific locations studied in this research.
APPROVED
Keywords: reading,; differentiated instruction,; differentiation,; teachers' understanding and implementation of DR; primary school,; elementary school; literacy